SEMANTICS AND PRAGMATICS OF FORMALLY TAUTOLOGICAL STATEMENTS IN DIALECT SPEECH - Golianych, Mariia; Varvaruk, Inna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The article reveals the actualization peculiarities of the meanings such formally tautological expressions as ч’олов’і́к йе ч’олов’і́к, жи́нка йе жи́нка, дити́на йе дити́на, жит′е́ йе жит′е́, which function in the speech of the village residents of Tyudiv; it is shown how the given language formulas, included in addressee-addressee relations, acquire different emotional-evaluative and communicative-pragmatic meanings; it is proved that the semantic content of these statements depends on the communication situation and is formed by the units of different language levels. It has been studied how the meanings of these units are actualized, which communicative intentions they verbalize under specific conditions of interaction, and which linguistic means are significant in their semantic content. It has been revealed that a tautological propositional structure used by the speaker often signals not only the thematic direction in which the communication is being developed — initiated by the communicative partner — but also indicates that, by opening the dialogic interaction, the speaker expects the interlocutor to express their own considerations regarding the semantic specification of this formula. It has also been established that such utterances may function as a semantic generalization of a certain thematic block during communication, as well as serve as a means that facilitates the development of a particular topic or shifts the interlocutor’s attention to another aspect of it.